Tuning the response of non-allowed Raman modes in GaAs nanowires. (1st February 2016) - Amaduzzi, Francesca; Alarcón-Lladó, Esther; Hautmann, Hubert; Tanta, Rawa; Matteini, Federico; Tütüncüoǧlu, Gözde; Vosch, Tom; Nygård, Jesper; Jespersen, Thomas; Uccelli, Emanuele; Fontcuberta i Morral, Anna
Abstract: We report on the use of photonic resonances in Raman spectroscopy on single nanowires for the enhancement of forbidden modes and the study of the interaction of phonons with free-carriers. This is achieved by suspending nanowire over a trench and detecting Raman scattered light with light polarized along the radial direction. Thanks to the photonic nature of the light–nanowire interaction, light polarization inside the nanowire is modified. This results in the excitation of LO modes, forbidden on {1 1 0} surfaces. We apply this new configuration to the measurement of carrier concentration on doped GaAs nanowires. These results open new perspectives for the study of the interaction of free-carriers or plasmons with optical phonons in nanostructures.